Axin phosphorylation in condensates counteracts tankyrase-mediated degradation - Klement, Katharina; Brückner, Martina; Bernkopf, Dominic (Journal of Cell Science, 2023)
Axin is a central negative regulator of the proto-oncogenic Wnt/β-catenin signaling pathway, as axin condensates provide a scaffold for the assembly of a multiprotein complex degrading β-catenin. Axin in turn is degraded via tankyrase. Consequently, small molecule tankyrase inhibitors block Wnt signaling by stabilizing axin, revealing potential for cancer therapy. Here, we discover phosphorylation of axin by casein kinase 1α (CK1α) at an N-terminal CK1 consensus motif, which was antagonized by protein phosphatase 1 (PP1). Axin condensates promoted phosphorylation by enriching CK1α over PP1. Importantly, the phosphorylation took place within the tankyrase-binding site, hindered axin-tankyrase interaction electrostatically and/or sterically, and counteracted tankyrase-mediated degradation of axin. Thus, the presented data propose a novel mechanism regulating axin stability, with implications for Wnt signaling, cancer therapy and self-organization of biomolecular condensates.<br
Keywords: Axin; Wnt signaling; Biomolecular condensates; Tankyrase